THE APPLICATION OF THINK-PAIR-SHARE STRATEGY IN IMPROVING STUDENTS’ SPEAKING ABILITY - Supraba Ardhy (Institut Agama Islam Negeri Palopo, 2018)
The aims of this research were to find out (1) the extent to which Think-Pair-Share strategy improves speaking ability of the fourth semester students of Cokroaminoto Palopo University; (2) the students’ perceptions on the application of Think-Pair-Share strategy in speaking activities. This research was carried out in the fourth semester students of English Language Education Study Program, Faculty of Teacher Training and Education, Cokroaminoto Palopo University. The method used was quasi-experimental research with pre-test, ten meetings of treatment, and post-test. The sample was selected through purposive sampling technique. The data were collected through speaking test, questionnaire, and recorder instruments, and were analyzed with nonparametric test and frequency test. The result of Mann-Whitney U test and the students’ score on post-test was p < 0.05. It means that, there is a significant difference between the students taught with Think-Pair-Share strategy and without Think-Pair-Share strategy. The mean score of experimental group on pretest was 2.16, and increased to be 4.02 on posttest. The analysis of questionnaire indicated that the students’ perceptions on the application of Think-Pair-Share strategy were very positive. Thus, it can be concluded that the application of Think-Pair-Share strategy could significantly improve the students’ speaking ability.